An integrated multiscale simulation guiding the processing optimisation for additively manufactured nickel-based superalloys - Xing He; Bing Yang; Decheng Kong; Kunjie Dai; Xiaoqing Ni; Zhanghua Chen; Chaofang Dong (Virtual and Physical Prototyping, 2024)
ABSTRACTMicrostructural defects in laser powder bed fusion (LPBF) metallic materials are correlated with processing parameters. A multi-physics model and a crystal plasticity framework are employed to predict microstructure growth in molten pools and assess the impact of manufacturing defects on plastic damage parameters. Criteria for optimising the LPBF process are identified, addressing microstructural defects and tensile properties of LPBF Hastelloy X at various volumetric energy densities (VED). The results show that higher VED levels foster a specific Goss texture {110} <001>, with irregular lack of fusion defects significantly affecting plastic damage, especially near the material surface. A critical threshold emerges between manufacturing defects and grain sizes in plastic strain accumulation. The optimal processing window for superior Hastelloy X mechanical properties ranges from 43 to 53 J/mm3. This work accelerates the development of superior strength-ductility alloys via LPBF, streamlining the trial-and-error process and reducing associated costs.